2020
DOI: 10.1038/s41598-020-70633-7
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA FENDRR regulates IFNγ-induced M1 phenotype in macrophages

Abstract: Macrophages play an essential role in host defense and display remarkable plasticity in switching between classically (pro-inflammatory—M1) and alternatively activated (anti-inflammatory—M2) phenotypes. The molecular mechanisms of macrophage polarization are not fully understood. Long non-coding RNAs (lncRNAs) with a length of > 200 nucleotides have been shown to play diverse roles in biological processes. Aberrant expression of lncRNAs is associated with a variety of pathophysiological conditions such as canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“… Liu and Du (2019) proved that FENDRR might work as a tumor suppressor gene in colon cancer by inhibiting SOX4. Also, FENDRR is closely related to immune regulation ( Munteanu et al, 2020 ; Shen et al, 2021 ). Moreover, FENDRR takes effect in different cancers, such as hepatocellular carcinoma, cholangiocarcinoma, gastric cancer, cervical cancer, breast cancer, prostate cancer, endometrial cancer, and non-small cell lung cancer ( He et al, 2018 ; Li et al, 2018 ; Qin et al, 2019 ; Yu et al, 2019 ; Zhang G. et al, 2019 ; Zhang Y.Q.…”
Section: Discussionmentioning
confidence: 99%
“… Liu and Du (2019) proved that FENDRR might work as a tumor suppressor gene in colon cancer by inhibiting SOX4. Also, FENDRR is closely related to immune regulation ( Munteanu et al, 2020 ; Shen et al, 2021 ). Moreover, FENDRR takes effect in different cancers, such as hepatocellular carcinoma, cholangiocarcinoma, gastric cancer, cervical cancer, breast cancer, prostate cancer, endometrial cancer, and non-small cell lung cancer ( He et al, 2018 ; Li et al, 2018 ; Qin et al, 2019 ; Yu et al, 2019 ; Zhang G. et al, 2019 ; Zhang Y.Q.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, the overexpression of FENDRR could enhance interferon γ (IFN γ) induced M1 macrophage polarization by modulating signal transducer and activator of transcription 1 (STAT1) activation pathway. 41 LncRNA LINC01116 was found to be dysregulated in various human cancers, such as glioma, prostate cancer, breast cancer, and osteosarcoma. [42][43][44][45] And recent studies also suggested that LINC01116 plays an oncogenic role in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage polarization : FENDRR was identified as a positive regulator of pro-inflammatory M1 macrophage polarization via the STAT1-dependent pathway [ 78 ]. Disorders associated with macrophage polarization include fibrosis [ 79 ], cancer [ 80 ], infections [ 81 ], insulin resistance [ 82 ], atherosclerosis [ 83 ], and autoimmune disease [ 84 ].…”
Section: Fendrr In Development and Diseasementioning
confidence: 99%